Determination of peak ordering in the CrCoNi medium-entropy alloy via nanoindentation. (December 2022) - Zhang, Mingwei; Yu, Qin; Frey, Carolina; Walsh, Flynn; Payne, Madelyn I.; Kumar, Punit; Liu, Dongye; Pollock, Tresa M.; Asta, Mark D.; Ritchie, Robert O.; Minor, Andrew M.
Abstract: Local chemical ordering (LCO) in the CrCoNi medium-entropy alloy was investigated by transmission electron microscopy (TEM) after different annealing treatments and their corresponding mechanical properties by bulk tensile tests and nanoindentation. A cold-rolled alloy was annealed at 1000°C for 0.5 h followed by ice water quenching and then aged at a number of different temperatures (600°C, 700°C, 800°C, 900°C, and 1000°C) under vacuum for 240 h to generate different degrees of chemical ordering. A splat-quenched sample rapidly cooled from the liquid phase was also examined. While bulk mechanical properties did not vary among samples with equivalent grain sizes, nanoindentation tests revealed notable differences. As indicated by the load at first pop-in using a Berkovich tip or the indentation yield strength via continuous stiffness measurements using a 10 μm spherical tip, the nanoindentation tests revealed that the stress for onset of plasticity during indentation varied with heat treatment and peaked in the 900°C aged sample. Energy-filtered TEM characterization indicated the presence of ordering in all specimens, with a higher degree of LCO in the aged samples relative to the splat-quenched and 1000°C-quenched samples. The evolution of LCO during aging was determined to occur on the time scale similar to those of bulk diffusion. The difference in nanoindentation strength was attributed to the difference in dislocation nucleation barriers imposed by different degrees of LCO. Graphical Abstract: Image, graphical abstract